(untitled) (Gestão & Regionalidade, 2024)
Abstract This article aims to analyze the vulnerability to consumption and social well-being, resulting from the tragedy that occurred because of the rupture of the B1 Dam, in Córrego do Feijão Mine, located in Brumadinho, Minas Gerais, where several lives were drained in the mud valley. The qualitative method was chosen for research, having the life history reports as a strategy to verify the data analysis, as it covers the interests involved in the exploratory phase, as well as a wealth of information absorbed in the involvement in the interviews with nine participants. Therefore, the main dimensions detected in the course of this work were: (a) suffering and losses; (b) family members’ means of subsistence; (c) the well-being of families and survivors; (d) the role of public authorities; (e) actions by Vale do Rio Doce with the affected families and with the community. Keywords: Vulnerability. Social welfare. Consumption.